From Spiritual Crisis to Ecological Ethics: Ecosufism, Religious Authority, and Environmental Governance in Indonesia - Rahman Hakim, Budi; Beck, Herman L.; Makruf, Jamhari (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2026)
Contemporary Islamic ecotheology has advanced environmental responsibility through institutional reform and ethical reinterpretation of classical principles such as khilāfa and amāna, yet it remains structurally limited by its predominant focus on behavioral compliance rather than the prior conditions of ecological perception. This study addresses that gap by developing Ecosufism as an analytically grounded framework that extends Islamic ecotheology toward a Sufi metaphysical account of the human-nature relationship. Drawing on hermeneutic analysis of classical Sufi sources alongside critical engagement with Nasr, Rosa, Latour, and Weber, the study operationalizes the Tawḥīd–Tazkiyya–‘Amal triad as a functional model specifying the mechanisms through which ontological awareness, ethical self-purification, and embodied ecological action constitute a coherent and sequential process of ecological consciousness. Indonesian cases, including the 2025 Ekoteologi Islam initiative, FNKSDA activism, and Neo-Sufi movements, illustrate the triad’s analytical range while revealing a consistent structural gap between the perceptual transformation Ecosufism prescribes and the institutional conditions required to sustain it at the collective scale. The study contributes an original analytical model that repositions ecological crisis as a problem of ontological perception within Islamic thought.